Work modes recognition and boundary identification of MFR pulse sequences with a hierarchical seq2seq LSTM. Issue 9 (24th July 2020) - Li, Yunjie; Zhu, Mengtao; Ma, Yihao; Yang, Jian
Abstract : Recognition of multi‐function radar (MFR) work mode in an input pulse sequence is a fundamental task to interpret the functions and behaviour of an MFR. There are three major challenges that must be addressed: (i) The received radar pulses stream may contain an unknown number of multiple work mode class segments. (ii) The intra‐mode and inter‐mode knowledge of a modern MFR may be too flexible and complicated to be represented and learned through traditional hand‐crafted features and learning models. (iii) The variable duration of each enclosed work mode makes the identification of the transition boundaries of adjacent modes difficult. To address these challenges and implement automatic recognition of MFR work mode sequences at a pulse‐level, this study develops a novel processing framework based on a time series representation of MFR work mode sequence and sequence‐to‐sequence (seq2seq) long short‐term memory network. The proposed method can not only automatically recognise multiple complexes modulated work mode classes in a pulse sequence. Still, it can also accurately identify the transition boundaries between each class by labelling the class information for each pulse. The experimental results showed the extended capabilities and improved performance of the proposed method over the state‐of‐the‐art work mode classification methods.